The impact of clinical and translational research on the quality of life during the metastatic colorectal cancer patient journey - Rodriguez Castells, Marta; Baraibar, Iosune; Ros, Javier; Saoudi, Nadia; Salvà, Francesc; García, Ariadna; Alcaraz, Adriana; Tabernero, Josep; Élez, Elena (Frontiers in Oncology, 2023)
The journey of metastatic colorectal cancer patients is complex and challenging, requiring coordination and collaboration between multiple healthcare providers. Understanding patients' needs, fears, feelings, concerns, and behaviors is essential for providing individualized patient-centered care. In recent years, mCRC patients have experienced improvements in clinical outcomes, from 16 months of overall survival to 32 months, thanks to research. However, there is still room for improvement, and integrating clinical and translational research into routine practice can help patients benefit from treatments and techniques that would not be an option. In the Journey of mCRC patients, living well with cancer and quality of life becomes a priority given the outcomes of the disease. Patient reported outcomes (PRO) and Patient Reported Outcomes Measures (PROMs) are becoming therefore new estimands in Oncology. Patient advocates represent important figures in this process by prioritizing issues and research questions; evaluating research designs and the performance of the research; the analysis and interpretation of data; and how results are disseminated. Multidisciplinary Tumor Boards and shared decision-making is essential for designing treatment strategies for individual patients. Quality of Life is often prioritized only when it comes to refractory advanced disease and end-of-life care, but it has to be integrated from the beginning, as the emotional impact of diagnosis leads to a vulnerable situation where patients' needs and preferences can be easily overseen. First-line treatment will be chosen among more treatment options than subsequent lines, with longer progression-free survival and a bigger impact on the outcomes. Practicing patient-centered care and optimizing first-line treatment for colorectal cancer patients requires a comprehensive understanding of patient experience and treatment outcomes, which can guide clinical practice and inform regulatory decisions for the benefit of patients.